Self-Care and Health-Related Quality of Life Among Heart Failure Patients in Tagus Valley Regional Hospital, Portugal: A Pilot Study - Seid SS; Amendoeira J; Ferreira MR (Dove Medical Press, 2022)
Sheka Shemsi Seid,1 José Amendoeira,2 Maria Regina Ferreira2 1School of Nursing, Faculty of Health Sciences, Institute of Health, Jimma University, Jimma, Ethiopia; 2Department of Nursing, Polytechnic Institute of Santarem, Quality of life Research Center, Santarem, PortugalCorrespondence: Sheka Shemsi Seid, Tel +251 911-298-479, Email sheka.shemsi@ju.edu.etIntroduction: Self-care has been suggested to improve heart failure patients´ health-related quality of life (HRQoL) and decrease the patient mortality rate. However, despite the growing importance of self-care and its obvious relationships with positive health outcomes, the evidence to justify its popularity among Portuguese heart failure (HF) patients is not well documented. Therefore, this study aimed to assess the extent of self-care behavior and level of HRQoL and to examine the relationships between self-care and HRQoL among HF patients.Methods: A descriptive correlational study design was conducted on 24 HF patients. Data were collected by using a validated Portuguese version of the Self-care Heart Failure Index (SCHFI V. 6.2) and the Minnesota Living with Heart Failure Questionnaire (MLHFQ). The data were analyzed using SPSS version 26. Descriptive, bivariate, and multivariate statistical tests were utilized. Pearson's correlation coefficient and multiple linear regression analysis were performed to determine the relationship between self-care behavior and health-related quality of life. Statistical significance was declared at p-value < 0.05.Results: The study participant's mean (± SD) age was 66.88 ± 12.8 years. The overall mean (± SD) score of self-care maintenance, management, and confidence were 47.77 ± 15.28, 54.38 ± 18.26, and 70.20 ± 17.64, respectively. Higher SCHFI scores indicate better self-care behavior and only self-care confidence reached the self-care adequacy cut-off point 70. The majority of the study participants 11 (45%) had a poor health-related quality of life. Being a male gender (βs =− 0.408, p = 0.049) and having New York Heart Association (NYHA) functional class IV (βs = − 0.689, p = 0.009) were associated with poor self-care management. Married marital status (βs = − 0.585, p = 0.021) and NYHA class III (βs = 2.612, p = 0.024) and class IV (βs = 2.416, p = 0.034) were associated with the poor emotional HRQol. Poor physical HRQoL was associated with poor self-care management (βs = − 2.111, p = 0.007) and better self-care maintenance was associated with a good emotional health-related quality of life.Conclusion: Study participants had inadequate self-care maintenance, self-care management, and poor health-related quality of life. Significant correlations were observed between self-care management and physical HRQoL as well as between self-care maintenance and emotional health-related quality of life. Further research with representative sample size and rigorous study designs is recommended to evaluate the correlation of self-care behavior and HRQoL and other predicting variables among patients with heart failure.Keywords: heart failure, self-care, self-management, quality of life, HRQoL, adult